Designing and implementing innovation incubators to foster creative pedagogies in early childhood education - Lee, Bih Ni; Connie Cassy Ompok (Zenodo, 2025)
This study explores the design and implementation of innovation incubators aimed at fostering creative pedagogies in early childhood education. Employing a synthesis-method, the research integrates primary data from case studies, quantitative creativity assessment metrics, and qualitative insights from educators and classroom practices. Findings reveal that innovation incubators support creativity by providing flexible learning environments, encouraging exploratory play, and promoting teacher collaboration. The study highlights the importance of contextual adaptation, ongoing professional development, and evidence-based strategies to effectively cultivate creativity in early learners through structured innovation frameworks.